O gerenciamento de projetos e o planejamento de operações de guerra do Exército brasileiro - Silva, Abner de Oliveira e (2012)
This research aims at verifying how the project management methodology proposed by the Project Management Institute - PMI can contribute to the modernization of the war operations planning methodology in the Brazilian Army. For this purpose, there is developed a comparative study between the processes of initiation and planning groups settled by PMI in its Project Management Body of Knowledge - PMBOK and the war operations planning methodology in the Brazilian Army, named as 'Estimate of Situation'. This work is based on bibliographic and documentary researches that include renowned authors such as Kerzner, Cleland, Vargas, Lima, Maximiano, Valeriano, Prado and Xavier and also relevant Brazilian Army doctrinal manuals relevant to the topic and the PMKO itself. In order to contextualize this work, it is made equivalence between a military war operation and a civilian project. The Estimate of Situation is characterized as a planning and decision making process similar to the set of processes of the project management from initiation and planning groups. As researches show that the areas of Cost, Human Resources and Acquisition, because of the war operation peculiarities, are treated in such a different manner than in project management, they are not included in this study. Furthermore, it is observed that the military planning process is executed mainly with the intuitiveness gathered in the application of tacit knowledge whereas in project management it is used several tools based on logic and mathematics what gives the planning process projects a greater degree of impartiality and accuracy. It is also verified that the military planning process produces a large number of graphic material allowing a 'graphical view' of various areas and aspects of the problem, facilitating the use of intuition in the decision making. Finally, after identifying the project management processes that concerns to this study and the peculiarities of the planning methodology used in the Brazilian Army, it is concluded, as supposed, that the methodology of project management has features that could effectively contribute to the modernization of the war operations planning in the Brazilian Army, named as Estimate of Situation. These resources are listed at the conclusion of this work.